CHANGING THE LANES TO OVERTAKE: EXPLORING CHINA’S STRATEGY OF INNOVATION - mai, jianjun (Journal Social Sciences and Humanioran Review, 2024)
This article explores China's strategic approach to development, known as Lane-Change Overtaking (Huandao Chaoche), which emphasizes innovation, differentiation, and systemic coordination to bypass traditional development stages. This strategy involves identifying new tracks and building sufficient driving force to achieve leadership, as exemplified by China's success in the electric vehicle industry and its surge in patent applications. The core principles of Lane-Change Overtaking include aligning internal development needs with global trends, breaking path dependence, fostering disruptive innovation, and building robust ecosystems. This paper adopts critical, analytical, and comparative approaches to conduct the study. The lessons derived from China's experiences offer valuable insights for developing nations, particularly Muslim countries, seeking to accelerate progress and enhance their global competitiveness. Key words: China; Development; Innovation; Lane-Change Overtaking, Strategy